2016
DOI: 10.3906/kim-1504-63
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of laccase onto a porous nanocomposite: application for textile dye degradation

Abstract: Poly(MA-alt-MVE)-g -PLA/ODA-MMT nanocomposite was prepared by self-catalytic interlamellar graft copolymerization of L-lactic acid (LA) onto poly(maleic anhydride-alt-methyl vinyl ether) copolymer in the presence of octadecyl amine-montmorillonite (ODA-MMT) organoclay. FTIR, 1 H ( 13 C) NMR, XRD, and SEM-TEM were utilized for characterizing the resultant nanocomposite. Laccase from Trametes versicolor was immobilized onto the prepared nanocomposite by adsorption or covalent coupling. Decolorization of Reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Among them, the broad peak at 3440 cm − 1 is the stretching vibration peak of the intermolecular hydrogen bond (υ OH ) of multi-molecule association [ 19 ]; the peak at 2920 cm − 1 is the stretching vibration peak of υ asCH , indicating that it contains a saturated hydrocarbon group -CH2 - [ 20 ]; The broad peak at 1050 cm − 1 is the stretching vibration peak of the hydroxyl group (υ C-O ), which may contain primary alcohols. The peak at 1645 cm − 1 in the infrared spectrum of FL represents the stretching vibration peak of C-H, indicating that it contains unsaturated hydrocarbon groups C=C [ 21 ]; the peak at 2850 cm − 1 in the infrared spectrum of CKMB is the stretching of υ sCH , indicating that it contains saturated hydrocarbon group -CH2-, which is a sign of the successful grafting of the quaternary ammonium cation in CTAB to the surface of biochar. In addition, the infrared spectra of laccase@CKMB all contained the above peaks, indicating that laccase was successfully immobilized on the surface of biochar.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the broad peak at 3440 cm − 1 is the stretching vibration peak of the intermolecular hydrogen bond (υ OH ) of multi-molecule association [ 19 ]; the peak at 2920 cm − 1 is the stretching vibration peak of υ asCH , indicating that it contains a saturated hydrocarbon group -CH2 - [ 20 ]; The broad peak at 1050 cm − 1 is the stretching vibration peak of the hydroxyl group (υ C-O ), which may contain primary alcohols. The peak at 1645 cm − 1 in the infrared spectrum of FL represents the stretching vibration peak of C-H, indicating that it contains unsaturated hydrocarbon groups C=C [ 21 ]; the peak at 2850 cm − 1 in the infrared spectrum of CKMB is the stretching of υ sCH , indicating that it contains saturated hydrocarbon group -CH2-, which is a sign of the successful grafting of the quaternary ammonium cation in CTAB to the surface of biochar. In addition, the infrared spectra of laccase@CKMB all contained the above peaks, indicating that laccase was successfully immobilized on the surface of biochar.…”
Section: Resultsmentioning
confidence: 99%
“…The morphology and microstructure of the TiO 2 -ZrO 2 and TiO 2 -ZrO 2 -SiO 2 oxide materials were evaluated based on SEM and TEM observations ( Figure 1). The obtained mixed oxide systems are characterized by non-spherical and irregular particles with nanometric size that tend to aggregation and agglomeration [27,28]. The TiO 2 -ZrO 2 system is characterized by aggregates with diameters of around 10 µm, whereas TiO 2 -ZrO 2 -SiO 2 material forms smaller aggregates, compared to a two-component oxide material, which size does not exceed 5 µm.…”
Section: Supports Characterizationmentioning
confidence: 99%
“…It was also reported that the Lac of Trametes versicolor immobilized for adsorption or covalent coupling in a nanocomposite has a greater decoloration capacity of Reactive Red 3 (about 65%) when compared with free Lac (33%). This happened because the superficial supports functionalized with reactive groups increase the loading capacity and the stability of the protein under study 102 . The efficiency of the immobilized Lac was also verified in the study by Daâssi et al ., 103 where the effects of the conditions of immobilization of the enzyme produced by C. gallica improved the stability, and therefore showed high efficiency to decolor the anthraquinone dye remazol brilliant blue R. This method also promotes a reduction in the cost of producing enzymes, making their application more economical in biotechnological processes.…”
Section: Biotechnological Applications Of Fungal Lmesmentioning
confidence: 99%